Exchange Policy and Misalignments in Morocco: A Quantitative Analysis - Pouya, Pascal; Karim, Mohamed; Arbia, Anass; El Yazidi, Mohammed; Sobhi, Khalid (International Journal of Economics and Financial Issues, 2024)
The research examines the equilibrium exchange rate and misalignment quantifications for the case of Morocco over the period 1990-2022. Based on an econometric model developed by Edwards in 1994, fundamental variables such as productivity, foreign direct investment (FDI), inflation and the real interest rate (RIR) are analysed to estimate the equilibrium value of the real exchange rate (REER) of the Moroccan dirham. The results show a cointegration between the REER and the fundamental variables, indicating the existence of a long-term relationship. The analysis of misalignments reveals periods of overvaluation and undervaluation of the Moroccan dirham, influenced by economic factors and monetary policies. This study has important implications for economic and monetary policy in Morocco, particularly with regard to export competitiveness and macroeconomic stability.